Implementation Of Contrastive Analysis To Overcome The Difficulties of Learning English Pronunciation Sub-Skill - Ristati; Bahing; Lesly Martha; Maida Norahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2020)
This research was conducted to investigate and understandpronunciation problems, which is the sub-skill of speaking in the first semester students of the UPR FKIP English Education Study Programthrough contrastive analysis. The purpose of this study was to analyzepronunciation errors in English words and the causes of the errors made bystudents who were the research subjects. The design used in this study topresent the data is descriptive qualitative. The results of data analysis wereclassified into consonant errors (consonants), vowels (vowels), and vowels(diphthongs) and the causes why these errors occured.Based on the results of data analysis, the English segmental soundsthat were difficult to pronounce by students of the English Education StudyProgram semester I in the academic year 2020/2021 were 1) long vowels ortense vowels (i:, u:, ?:, ?:, ?:]; 2) short vowels soundor lax vowels lowvowel sound [æ], and neutral vowel (schwa) [?]; 3) the sound of diphthongs(double vowels), namely rising diphthongs [??] and falling diphthongs [??],[e?], and [??]; and 4) fricative consonant sounds [f, v, z, ?, ð, ?, ?].The causes of difficulty in learning pronunciation of Englishsegmental sounds are 1) differences in Indonesian and English soundsystems and 2) lack of knowledge of the English sound system.